Cascade control for feed drive systems - Nam, Ngo Hong; Phuong, Tran Thuy Uyen; Chuong, Vo Lam; Vu, Truong Nguyen Luan (Vietnam Journal of Mechanics, 2025)
In the machining industry, the demands for precision and high speed of machine tools in CNC machines are increasingly high. The crucial component of these kinds of machines is a feed drive (FD) system, which comprises a servo motor coupled with a ball screw. Therefore, in this paper, a cascade scheme consisting of an inner and outer loop, which are also called the secondary and primary loops respectively, is suggested to control the feed drive system to improve the system's performance regarding tracking control and disturbance rejection. A filtered proportional integral (PI) controller is suggested for the secondary loop, and its tuning guidelines are established through the internal model control (IMC) approach. Additionally, a fractional-order proportional derivative (FOPD) controller and its design methodology in the frequency domain are introduced for the primary loop. The robust stability of the controlled system is assured by the maximum sensitivity function (Ms value). The investigation carried out through simulation focused on the feed drive system, and the findings indicated that the suggested control strategies fulfill the stringent criteria of a servo system.